A rat model of nerve stimulator-guided brachial plexus blockade. (April 2019) - Zhang, Yanzi; Cui, Bo; Gong, Chunyu; Tang, Yidan; Zhou, Jianxiong; He, Yi; Liu, Jin; Yang, Jing
It is important to develop a feasible animal model of regional anesthesia other than sciatic nerve blockade for pharmacokinetic investigations of new local anesthetics or analgesia in upper extremity surgery. Herein, we explored a nerve stimulator (NS)-guided brachial plexus block (BPB) in a rat model. The anatomy of the brachial plexus in rats was delineated in cadavers, and various BPBs were examined. The puncture point was located 0.5–1.0 cm below the lateral one-third of the clavicle. The efficacy and safety of the NS-guided BPB were evaluated using an injection of 2% lidocaine or 0.5% bupivacaine in 16 live animals; saline injection was used as a control. Both sides of the brachial plexus were located successfully using the NS-guided technique. Sensory blockade (nociception assessment) and motor blockade (grasping and straightening tests) appeared after application of the two classical local anesthetics, but not normal saline. The motor and sensory blockade induced by bupivacaine exhibited a longer duration than that induced by lidocaine ( p < 0.05). All rats recovered uneventfully from general anesthesia and BPB. No abnormal results were found in pathological studies or behavioral observations. Thus, a rat model of NS-guided BPB was established, and BPB induced an overall reversible sensory and motor blockade in the thoracic limbs. Evaluation of the efficacy and safety demonstrated that this rat BPB model was feasible, reproducible, and safe.